2001
DOI: 10.1177/153537020222600812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypergravity Exposure on the Developing Central Nervous System: Possible Involvement of Thyroid Hormone

Abstract: The present study examined the effects of hypergravity exposure on the developing brain and specifically explored the possibility that these effects are mediated by altered thyroid status. Thirty-four timed-pregnant Sprague-Dawley rats were exposed to continuous centrifugation at 1.5 G (HG) from gestational Day 11 until one of three key developmental points: postnatal Day (P) 6, P15, or P21 (10 pups/dam: 5 males/5 females). During the 32-day centrifugation, stationary controls (SC, n = 25 dams) were housed In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…While a number of chemicals (Nguon et al, 2005a) have been shown to affect the developing CNS structure and function, our own previous studies suggested that the developing CNS may also be vulnerable to altered gravity (Sajdel-Sulkowska et al, 2001;Nguon et al, 2004;Sulkowski et al, 2004;Nguon et al, 2005b). Impairment in motor coordination observed in rat neonates developing under hypergravity was accompanied by changes in cerebellar structure.…”
Section: Introductionmentioning
confidence: 87%
“…While a number of chemicals (Nguon et al, 2005a) have been shown to affect the developing CNS structure and function, our own previous studies suggested that the developing CNS may also be vulnerable to altered gravity (Sajdel-Sulkowska et al, 2001;Nguon et al, 2004;Sulkowski et al, 2004;Nguon et al, 2005b). Impairment in motor coordination observed in rat neonates developing under hypergravity was accompanied by changes in cerebellar structure.…”
Section: Introductionmentioning
confidence: 87%
“…Results of these studies have shown that exposure to hypergravity (1.5 G) during the perinatal period, including the critical brain development period (P5-P10), affects both the pregnant dams (Ladd et al 2006) and neonates (Sajdel-Sulkowska et al 2001). Pregnant rat dams exposed to hypergravity show lower food consumption, lower weight gain, and altered pregnancy outcome.…”
Section: Cerebellar Development Under Altered Gravitymentioning
confidence: 98%
“…Results of our studies have indicated that the mass of the forebrain and the mass of the cerebellum were maximally reduced on P6 by 15.9% and 25.6% respectively. The results of three way ANOVA, with gravitational condition, age and either body, forebrain or cerebellar mass as a factor suggested that the effect of hypergravity on the CNS is independent of the effect on body mass and that the changes in the forebrain and the cerebellum are independent of each other (19). Results of our studies also suggest a biphasic nature of changes in the cerebellum, with the first downward deviation from control in cerebellar mass between P6 and P9 and a second around P21.…”
Section: Gravireaction To Hypergravitymentioning
confidence: 92%
“…This is suggested by observations that prenatal exposure of rats to microgravity affects the righting response (15) and motor and equilibrium behavior that are associated with structural changes in the brain (16). Cerebellar abnormalities are frequently associated with deficits in motor functions (17) and cerebellar abnormalities have been observed both under microgravity and hypergravity (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Gravireaction Of the Mature Cnsmentioning
confidence: 99%
See 1 more Smart Citation